2004
DOI: 10.1182/blood-2004-01-0373
|View full text |Cite
|
Sign up to set email alerts
|

Primary human CD34+ hematopoietic stem and progenitor cells express functionally active receptors of neuromediators

Abstract: Recently, overlapping molecular phenotypes of hematopoietic and neuropoietic cells were described in mice. Here, we examined primary human CD34 ؉ hematopoietic stem and progenitor cells applying specialized cDNA arrays, real-time reverse-transcriptase-polymerase chain reaction (RT-PCR), and fluorescent-activated cell sorter (FACS) analysis focusing on genes involved in neurobiologic functions. We found expression of vesicle fusion and motility genes, ligand-and voltage-gated ion channels, receptor kinases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 61 publications
5
79
0
Order By: Relevance
“…Results with hematopoietic stem cells and CD34 positive hematopoietic progenitors have shown, that these cells express genes that are expressed in neural and various other normal nonhematopoietic tissues (Luce and Burrows, 1999;Akashi et al, 2003;Goolsby et al, 2003;Georgantas et al, 2004;Steidl et al, 2004). Skeletal muscle stem cells express neural stem cell genes and adult bone marrow-derived mesenchymal stem cells express different mesenchymal genes as well as genes of various other lineages including neuronal, testis, liver, lung, hematopoietic and endothelial tissues (Woodbury et al, 2002;Seshi et al, 2003).…”
Section: Epigenetic Control Of Gene Expressionmentioning
confidence: 99%
“…Results with hematopoietic stem cells and CD34 positive hematopoietic progenitors have shown, that these cells express genes that are expressed in neural and various other normal nonhematopoietic tissues (Luce and Burrows, 1999;Akashi et al, 2003;Goolsby et al, 2003;Georgantas et al, 2004;Steidl et al, 2004). Skeletal muscle stem cells express neural stem cell genes and adult bone marrow-derived mesenchymal stem cells express different mesenchymal genes as well as genes of various other lineages including neuronal, testis, liver, lung, hematopoietic and endothelial tissues (Woodbury et al, 2002;Seshi et al, 2003).…”
Section: Epigenetic Control Of Gene Expressionmentioning
confidence: 99%
“…Recently, we have shown that genes primarily expressed in the nervous system may also be expressed in normal human CD34 þ cells (Steidl et al, 2004). This finding prompted us to examine our CML CD34 þ cells with regard to the expression of genes involved in neurobiological functions.…”
Section: Expression Of G Protein-coupled Neurobiological Receptorsmentioning
confidence: 99%
“…Since we have previously shown that the expression of those receptors on normal CD34 þ cells depends on the coexpression of CD38 (Steidl et al, 2004), we assessed the proportions of CD34 þ cells with low or high CD38 expression. Comparing CML CD34 þ cells with normal CD34 þ cells, we found a similar proportion of CD38 low expressing cells in both groups (4.26% (mean) vs 4.33% (mean)), indicating that differential expression of G protein-coupled receptors is not the result of a different composition of the CD34 þ cell population with regard to maturation state.…”
Section: Expression Of G Protein-coupled Neurobiological Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports indicate an overlap in the molecular programs for hematopoiesis and neuropoiesis in mice (14,15). Another report has shown that primary CD34ϩ hHSCs express mRNA for a number of proteins that are used by (among other cell types) neurons, including receptors for trophic factors and other mediators that are known to influence the development of neurons (16). Commonalities in the expression profiles of neural and HSCs provide molecular opportunities for across-tissue differentiation, but it remains to be seen how well these can be used in the organism or exploited in the clinic.…”
mentioning
confidence: 99%